The decline in stroke hospitalization due to COVID‐19 is unrelated to COVID‐19 intensity. (28th December 2022) - Sedova, Petra; Kent, Julia Anna; Bryndziar, Tomas; Jarkovsky, Jiri; Tomek, Ales; Sramek, Martin; Skoda, Ondrej; Sramkova, Tereza; Pokorová, Kateřina; Littnerova, Simona; Brown, Robert D.; Mikulik, Robert
Abstract: Background and Purpose: During the coronavirus disease 2019 (COVID‐19) pandemic many countries reported a decline in stroke volumes. The aim of this study was to analyze if the decline was related to the intensity of the COVID‐19 pandemic. Methods: The first pandemic year (1 March 2020 to 28 February 2021) overall and during the three COVID‐19 waves were compared with the preceding year. Volumes of acute ischaemic stroke (AIS), subarachnoid hemorrhage, intracerebral hemorrhage and recanalization treatments (intravenous thrombolysis [IVT] and mechanical thrombectomy [MT]) were obtained from the National Register of Reimbursed Health Services. Door‐to‐needle time, onset‐to‐door time and National Institutes of Health Stroke Scale at admission were obtained from the Registry of Stroke Care Quality. Results: During the pandemic year compared to the preceding year there were 26, 453 versus 28, 771 stroke admissions, representing an 8.8% decline ( p  < 0.001). The declines (−10%, −11%, −19%) appeared in COVID‐19 waves (spring 2020, autumn 2020, winter 2021) except for an increase (2%) during summer 2020. Admissions for AIS declined by 10.2% ( p  < 0.001), whilst hemorrhagic stroke volumes were minimally decreased. The absolute volumes of IVT and MT decreased by 9.4% ( p  < 0.001) and 5.7% ( p  = 0.16), respectively. However, the proportions of ischaemic stroke patients receiving IVT (18% vs. 18%; p  = 0.72) and MT (6% vs. 6%; p  = 0.28) remained unchanged. Conclusions: There was a decline in stroke admissions, but such decline was not related to COVID‐19 incidence. The frequency of use of recanalization procedures (IVT, MT) and times (onset‐to‐door time, door‐to‐needle time) in AIS were preserved in the Czech Republic during the first year of the pandemic.